(untitled) (Research, Society and Development, 2021)
The perspectives of thoughts of Frankl’s Logotherapy and Existential Analysis and Freud’s Psychoanalysis, despite different views of the human being and the world, there is much in common, especially when the influences of humanism and existentialism affect the thoughts of psychoanalysts. This work aims to present the theoretical assumptions about love and humanity of Viktor Emil Frankl and Erich Fromm, considered two humanists. The article seeks to indicate, regardless of the divergences between the two psychological approaches, common positions of similar thoughts, that is, agreement of ideas in benefit of a common good of the individual’s mental health in therapy. Bibliographic research in books and articles in databases was used, through the theoretical foundations of the thoughts of Viktor Emil Frankl and Erich Fromm. It was found that, even from divergent schools in relation to the concepts of human being and world, the two approaches presented, according to the thinkers, perspectives that converge in relation to the constructs of love and humanity.